Porous membranes, methods of making porous membranes, and structures

By coating the surface of the nanomaterial with an organosilane compound and cross-linking treatment, the problem of insufficient light transmittance and hydrophobicity of the nanomaterial structure in the prior art is solved, and a porous film or porous material with high light transmittance and hydrophobicity is realized.

CN119731117APending Publication Date: 2025-03-28SONY GROUP CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380050757.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-05
Filing Date
2023-05-17
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

It is difficult to develop nanomaterial structures with high light transmittance and hydrophobicity, especially when making porous membranes or porous materials.

Method used

The nanomaterial is coated with an organosilane compound on the surface of the nanomaterial and crosslinking the nanomaterials with a crosslinking agent to form a waterproof porous membrane or porous material.

Benefits of technology

The high light transmittance and hydrophobicity of the nanomaterial structure are achieved, the aggregation of nanoparticles or fibers is avoided, and the transparency and anti-fouling properties of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119731117A_ABST
    Figure CN119731117A_ABST
Patent Text Reader

Abstract

The present invention provides a nanomaterial structure comprising a nanomaterial, the nanomaterial comprising a nanomaterial surface; an organosilane compound provided on the surface of the nanomaterial; and a nanomaterial cross-linking part, wherein the nanomaterial is cross-linked with the nanomaterial cross-linking part.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Related Applications

[0002] This application claims the benefit of Japanese Priority Patent Application JP 2022-108615 filed on Jul. 5, 2022, the entire contents of which are incorporated herein by reference. Technical Field

[0003] The present disclosure relates to hydrophobic porous membranes or porous materials comprising nanomaterials (eg, nanoparticles, nanofibers, nanosheets, or other nanomaterials of suitable size and shape), methods of making the porous membranes or porous materials, and structures, for example. Background Art

[0004] For example, Patent Document 1 discloses a silica aerogel having hydrophobicity and oleophobicity and having a density in the range of 0.005 g / cc to 0.5 g / cc. The silica aerogel has a silica surface which is formed by contacting with a (SiO2) m The invention relates to a method for fluorine treatment by chemically reacting a gel-like compound of silica having a silanol group-containing fluoroalkyl silane compound (m is a positive integer), wherein the fluoroalkyl silane compound comprises a fluoroalkyl group and a functional group capable of reacting with the silanol group.

[0005] Reference List

[0006] Patent Literature

[0007] [PTL 1] Japanese Unexamined Patent Application Publication No. 2001-72408 Summary of the invention

[0008] Technical issues

[0009] Hydrophobic nanomaterial structures including nanomaterials (eg, porous films or porous materials) are desirable, for example, to have improved light transmittance.

[0010] For example, it is desirable to provide a nanomaterial structure including a nanomaterial (eg, a porous film or a porous material) having high light transmittance and hydrophobicity, as well as a method of manufacturing the nanomaterial and the nanomaterial structure.

[0011] Solution to the problem

[0012] The present disclosure relates to nanomaterial technology.

[0013] In an embodiment, a nanomaterial structure is provided. The nanomaterial structure includes a nanomaterial including a nanomaterial surface; an organic silane compound provided on the nanomaterial surface; and a nanomaterial crosslinking portion, wherein the coated nanomaterial is crosslinked with the nanomaterial crosslinking portion.

[0014] In an embodiment, a porous membrane or a porous material is provided and includes a nanomaterial, the nanomaterial including a nanomaterial surface; an organic silane compound provided on the nanomaterial surface; and a nanomaterial crosslinking portion, wherein the nanomaterial is crosslinked with the nanomaterial crosslinking portion.

[0015] In an embodiment, a method for manufacturing a nanomaterial structure is provided. The method includes providing a nanomaterial including a nanomaterial surface; and providing an organosilane compound on the nanomaterial surface to form a coated nanomaterial. In a further embodiment, the method includes: providing a crosslinking agent; and forming a nanomaterial crosslinked structure by crosslinking the coated nanomaterial with the crosslinking agent. In another embodiment, the method includes drying the nanomaterial crosslinked structure. In another embodiment, the method includes forming a porous membrane or a porous material from the nanomaterial crosslinked structure. In another embodiment, the method includes forming a product from the nanomaterial crosslinked structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] [ Figure 1 ] Figure 1 is a schematic diagram of an example of a profile configuration of a porous membrane according to an embodiment of the present disclosure.

[0017] [ Figure 2A ] Figure 2A yes Figure 1 Schematic diagram of an example of a nanoparticle structure is shown.

[0018] [ Figure 2B ] Figure 2B yes Figure 1 A schematic diagram of another embodiment of the structure of a nanoparticle is shown in FIG.

[0019] [ Figure 3 ] Figure 3 It shows Figure 1 The characteristic diagram showing the relationship between the transmittance of the porous film and the particle size.

[0020] [ Figure 4 ] Figure 4 This is an image diagram of the porous membrane according to the embodiment of the present invention taken using a transmission electron microscope.

[0021] [ Figure 5A ] Figure 5A is using Figure 2A Schematic diagram of an embodiment of aspects of connection between nanoparticles in the case of nanoparticles shown in FIG.

[0022] [ Figure 5B ] Figure 5B is using Figure 2B Schematic diagram of another embodiment of aspects of connection between nanoparticles in the case of nanoparticles shown in FIG.

[0023] [ Fig. 6A ] Fig. 6A is an explanatory diagram of the conditions of the cross-linking portion in which nanoparticles connected to each other are not aggregated.

[0024] [ Figure 6B ] Figure 6B is an explanatory diagram of the conditions of the cross-linking portion in which nanoparticles connected to each other are not aggregated.

[0025] [ Figure 7 ] Figure 7 It is shown Figure 1 Flow chart of the porous membrane fabrication steps shown.

[0026] [ Figure 8 ] Figure 8 is a schematic diagram of an example of an outline configuration of a porous membrane according to a modification example of the present disclosure.

[0027] [ Fig. 9 ] Fig. 9 is a schematic diagram of another example of the schematic configuration of the porous membrane according to the modification example of the present disclosure. DETAILED DESCRIPTION

[0028] Hereinafter, embodiments of the present technology will be described in detail with reference to the accompanying drawings. The following description is only a specific embodiment of the present disclosure, and the present disclosure should not be limited to the following aspects. In addition, the present disclosure is not limited to the arrangement, size, size ratio, etc. of each component shown in the accompanying drawings. It should be noted that the description is given in the following order.

[0029] 1. Embodiment (Example of a hydrophobic porous membrane including a plurality of nanoparticles connected to each other via a cross-linking portion)

[0030] 1-1. Structure of porous membrane

[0031] 1-2. Method for producing porous membrane

[0032] 1-3. Work and Effect

[0033] 2. Modification Example (Another Example of the Porous Membrane)

[0034] <1. Implementation Method>

[0035] (1-1. Configuration of porous membrane)

[0036] Figure 1An example of the configuration of a porous membrane (porous membrane 1) according to an embodiment of the present disclosure is schematically shown. For example, the porous membrane 1 is used as an anti-reflection film and a protective sheet for preventing dripping, staining, and rust, and preventing the adhesion of fingerprints, imparting lubricity, and maintaining the texture of the material. The porous membrane 1 of this embodiment includes an organic silane molecule 12 ( Figure 2A In the porous membrane 1, the surface is coated with a plurality of nanoparticles 11 ( Figure 2B ) are connected to each other through the cross-linking portion 21.

[0037] The nanoparticles 11 are, for example, silicon dioxide particles. Figure 2A As shown, the nanoparticles 11 are surface-deactivated by reacting with an organosilane molecule 12 including an organic functional group or a fluorine group. Alternatively, the nanoparticles 11 are surface-deactivated by reacting with an organosilane molecule 12 including an organic functional group or a fluorine group and also including a reactive functional group 13, for example Figure 2B This makes the plurality of nanoparticles 11 unable to covalently bond with each other.

[0038] The thickness of the beaded skeleton forming the porous membrane 1 affects the transparency (light transmittance) of the porous membrane 1. The thickness of the skeleton corresponds to the particle size of the nanoparticles 11; a thinner skeleton results in less scattering of light, thereby improving transparency. The average particle size (median diameter) of the nanoparticles 11 is preferably, for example, a diameter of 11 nm or less, and more preferably a diameter of 7 nm or less. Thus, for example, Figure 3 As shown, when the plurality of nanoparticles 11 inside the porous membrane 1 have the most densely packed structure, a light transmittance of more than 70%, or a light transmittance of more than 90%, can be obtained, which is equivalent to the light transmittance of glass or plastic.

[0039] The average particle size (median diameter) of the nanoparticles 11 is determined as described below. First, the porous membrane 1 as a measurement target is processed to perform thin filming by a focused ion beam (FIB) method or the like. In the case of using the FIB method, a carbon film and a tungsten film are formed as a protective film as a treatment before observing a transmission electron microscope (TEM) image of a cross section described later. The carbon film is formed on the surface of the porous membrane 1 by a vapor deposition method. The tungsten film is formed on the surface of the porous membrane 1 by a vapor deposition method or a sputtering method. This allows the cross section of the porous membrane 1 to be formed by thinning.

[0040] The cross section of the obtained thinned sample was cross-sectionally observed using a transmission electron microscope (Tecnai G2 manufactured by FEI Ltd.) so that a plurality of nanoparticles 11 could be observed at an accelerating voltage of 200 kV and at a field of view of 50 nm×50 nm, thereby taking a TEM photograph. It was assumed that the photographing position was randomly selected from the thinned sample.

[0041] Next, 50 nanoparticles 11 whose diameters can be clearly confirmed in the direction of the observed surface are selected from the taken TEM photos. In the case where the number of nanoparticles 11 whose diameters can be clearly confirmed in one field of view captured is less than 50, 50 nanoparticles 11 whose diameters can be clearly confirmed in the direction of the observed surface are selected from multiple fields of view. Figure 4 is an image diagram of a TEM photograph of a porous membrane 1 taken using a transmission electron microscope. Figure 4 Among them, nanoparticles a and nanoparticles b whose diameters can be clearly confirmed are selected. Meanwhile, for example, for nanoparticles c and nanoparticles d, nanoparticles 11 overlap each other in the depth direction of observation and their shapes cannot be confirmed, and therefore nanoparticles c and nanoparticles d are not suitable as measurement objects. The maximum diameter of each of the selected 50 nanoparticles 11 is measured.

[0042] Herein, it is assumed that the maximum diameter is the maximum distance (referred to as the maximum Feret diameter) between two parallel lines drawn from all angles to be tangent to the outline of the nanoparticle 11. When measuring the maximum diameter (maximum Feret diameter), the diameter of the particle portion other than the coating portion (organosilane molecule 12) coating the surface of the nanoparticle 11 is measured. Determining the median of the 50 maximum diameters (maximum Feret diameters) thus determined allows the average particle size (median diameter) of the nanoparticle 11.

[0043] As described above, the organosilane molecule 12 is used to inactivate the surface of the nanoparticle 11 to prevent the bonding between the plurality of nanoparticles 11. The organosilane molecule 12 forms a covalent bond with the nanoparticle 11, and includes an organic functional group or a fluorine group. The surface of the nanoparticle 11 is coated with the organosilane molecule 12 having an organic functional group or a fluorine group, thereby making the surface of the nanoparticle 11 waterproof. In particular, coating the surface of the nanoparticle 11 with the organosilane molecule 12 including a fluorine group makes it possible to impart not only hydrophobicity but also oleophobicity.

[0044] Examples of the organosilane compound including an organic functional group or a fluorine group include organosilane compounds represented by the following general formula (1) or general formula (2).

[0045] (Chemical Formula 1) R 1 x Si(OR2 ) 4-x (1)

[0046] (Chemical formula 2) R 1 x SiCl 4-x (2)

[0047] (R 1 It is any one of methyl, ethyl, propyl, isopropyl, butyl, pentyl, hexyl, heptyl, octyl, decyl, dodecyl, hexadecyl, vinyl, phenyl, 1H,1H,2H,2H-tridecafluorooctyl, 1H,1H,2H,2H-heptadecafluorodecyl, pentafluorophenyl, 1H,1H,2H,2H-nonafluorohexyl, 3-(2,3,4,5,6-pentafluorophenyl)propyl, 11-pentafluorophenoxyundecyl and 5,5,6,6,7,7,7-heptafluoro-4,4-bis(trifluoromethyl)heptyl. 2 R is any one of methyl, ethyl, propyl and isopropyl. 2 is any one of methyl, ethyl, propyl and isopropyl. X is an integer of 0 or 2 or less.

[0048] It should be noted that, for example, the presence or absence of the organosilane molecules 12 coating the surface of the nanoparticles 11 and the aspect of the bonding between the nanoparticles 11 and the organosilane molecules 12 can be confirmed by component analysis or composition analysis. Examples of component analysis and composition analysis include Fourier transform infrared spectroscopy (FT-IR), gas chromatography (GC), X-ray photoelectron spectroscopy (XPS), nuclear magnetic resonance analysis (NMR), and energy dispersive X-ray analysis (EDX). The presence or absence of the organosilane molecules 12 coating the surface of the nanoparticles 11 and the aspect of the bonding between the nanoparticles 11 and the organosilane molecules 12 can be analyzed using one or more of the above-mentioned analysis methods.

[0049] As described above, the crosslinking portion 21 allows the plurality of nanoparticles 11 to be bonded to each other. Specifically, the crosslinking portion 21 is an organic substance or an inorganic substance that is directly covalently bonded to the nanoparticle 11, for example Figure 5A Optionally, the crosslinking portion 21 is an organic or inorganic substance that is indirectly covalently bonded to the nanoparticle 11 via an organic silane group (organosilane molecule 12), for example, Figure 5B The cross-linking portion 21 forms a covalent bond with one or two nanoparticles 11 .

[0050] The length of the crosslinking portion 21 is preferably less than, for example, half (1 / 2) of the average particle size (diameter) of the nanoparticles 11. Specifically, Fig. 6AAs shown in FIG. 1 , the length of the crosslinking portion 21 is preferably a length that is not in contact with the nanoparticle 11B and the nanoparticle 11C when the two nanoparticles 11B and 11C are connected to the one nanoparticle 11A at the farthest position (diagonal position) via the crosslinking portion 21. That is, the length of the crosslinking portion 21 is preferably less than the circumference of 60° (=π / 6 of the diameter) of the nanoparticle 11 (11A), as shown in FIG. Figure 6B This makes it possible to prevent the plurality of nanoparticles 11 from aggregating within the porous membrane 1 .

[0051] Examples of such crosslinking portion 21 include a crosslinking agent having two or more reaction points. Among those described above, examples of the crosslinking agent that directly forms a covalent bond with the nanoparticle 11 include silane compounds represented by the following general formula (3), general formula (4), general formula (5) or general formula (6).

[0052] (Chemical formula 3) R 3 Y Si(OR 4 ) 4-Y (3)

[0053] (Chemical formula 4) R 3 Y SiCl 4-Y c(4)

[0054] (Chemical Formula 5) (R 4 O) 3-Y R 3 Y Si-R 5 -SiR 3 Y (OR 4 ) 3-Y (5)

[0055] (Chemical formula 6)Cl 3-Y R 3 Y Si-R 5 -SiR 3 Y Cl 3-Y (6)

[0056] (R 3 is any one of a hydrogen atom, a methyl group, an ethyl group, a propyl group, an isopropyl group and a phenyl group). 4 R is any one of methyl, ethyl, propyl and isopropyl. 5 is any one of methylene, ethylene, propylene, butylene, pentylene, hexylene and phenylene. Y is an integer of 0 or less).

[0057] Examples of crosslinking agents that are indirectly covalently bonded to the nanoparticles 11 via an organosilyl group (organosilane molecule 12) include those crosslinking agents that include two or more reactive functional groups that react with the functional groups of the organosilane molecule 12. Examples of such crosslinking agents include multifunctional allyl (vinyl) groups, multifunctional thiols, multifunctional (meth) acrylates, and multifunctional glycidyl groups.

[0058] Specific examples of the multifunctional allyl (vinyl) groups include diallyl ether, diallyl sulfide, diallylamine, diallyl adipate, diallyldimethylsilane, diallylisophthalate, diallylurea, dimethyldivinylsilane, tetramethyldivinyldisiloxane, hexadiene, tetraallyloxyethane, triallylcyanurate and triallylamine.

[0059] Specific examples of the multifunctional thiol include ethanedithiol, propylenedithiol, hexanedithiol, pentaerythritol tetrakis(thioglycolate), pentaerythritol tetrakis(3-mercaptobutyrate), 1,4-bis(3-mercaptobutyryloxy)butane, 1,3,5-tris(2-(3-sulfanylbutyryloxy)ethyl(-1,3,5-triazinane-2,4,6-trione), and trimethylolpropane tris(3-mercaptobutyrate).

[0060] Specific examples of the multifunctional (meth)acrylate include diethylene glycol dimethacrylate, ethylene glycol dimethacrylate, tetraethylene glycol diacrylate, diethylene glycol diacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol tetraacrylate, and pentaerythritol tetraacrylate.

[0061] Specific examples of the multifunctional glycidol include glycidyl ether type epoxy resins such as bisphenol A diglycidyl ether, bisphenol F diglycidyl ether or resorcinol diglycidyl ether, phthalic acid diglycidyl ester and dimer acid diglycidyl ether, triglycidyl ether triphenylmethane, tetraglycidyl ether tetraphenylethane, bisphenol S diglycidyl ether, cresol novolac glycidyl ether, isocyanuric acid triglycidyl ether and tetrabromobisphenol A diglycidyl ether.

[0062] The air gap G formed in the porous membrane 1 includes, for example, continuous pores. The pores have, for example, an average pore size of several nanometers to several tens of nanometers. This enables the porous membrane 1 to obtain a fine sponge-like overall structure. It should be noted that although air is usually present inside the air gap G, the air gap G may be evacuated, or, for example, a gas having a thermal conductivity lower than that of air, such as helium (He) or argon (Ar), may be encapsulated therein, thereby further reducing the thermal conductivity of the porous membrane 1.

[0063] In the porous membrane 1, for example, 1 to 4 or more nanoparticles 11 are closest to one nanoparticle 11. For example, in the case where four nanoparticles are closest to one nanoparticle 11 inside the porous membrane 1, the porous membrane 1 has a diamond structure, and its porosity is 66% or more.

[0064] For example, the number of nanoparticles 11 closest to one nanoparticle 11 can be confirmed as follows. First, as in the case of measuring the average particle size (median particle size) of the nanoparticles 11 described above, the porous membrane 1 as the object of measurement is processed by the FIB method or the like to be thinned. A cross-sectional observation of the cross section of the obtained thinned sample is performed using a transmission electron microscope (Tecnai G2 manufactured by FEI Ltd.) so that a plurality of nanoparticles 11 can be observed at an accelerating voltage of 200 kV and at a field of view of 50 nm×50 nm, thereby taking a TEM photograph. It is assumed that the shooting position is randomly selected from the thinned sample.

[0065] Next, 50 nanoparticles 11 whose diameters can be clearly confirmed in the direction of the observation surface are selected from the captured TEM photographs. In the case where the number of nanoparticles 11 whose diameters can be clearly confirmed in the direction of the observation surface in one captured field of view is less than 50, 50 nanoparticles 11 whose diameters can be clearly confirmed in the direction of the observation surface are selected from multiple fields of view. For example, Figure 4 Among them, nanoparticles e and nanoparticle f whose diameters can be clearly confirmed in the direction of the observation surface are selected. Meanwhile, for example, with respect to nanoparticles c and nanoparticles d, the particles overlap each other in the depth direction of observation, and the positions of the particles cannot be correctly confirmed, and therefore nanoparticles c and nanoparticles d are not suitable as measurement targets.

[0066] For each of the selected 50 nanoparticles 11, the number of nanoparticles (e.g., nanoparticles e-1, e-2 and e-3 and nanoparticles f-1, f-2, f-3 and f-4) present at a position closer than a certain distance from the nanoparticle (e.g., nanoparticle e and nanoparticle f) is measured. Here, it is assumed that the certain distance is 0.5 times the diameter of the nanoparticle 11 as the maximum value of the length of the crosslinking portion 21. It is difficult to directly confirm the existence of the crosslinking portion 21 because its image is not taken by an electron microscope. However, in the absence of the crosslinking portion 21, it is impossible to maintain a structure in which the nanoparticles 11 are combined with each other. Therefore, it can be considered that the crosslinking portion 21 exists between the nanoparticles 11 and the nanoparticles 11. That is, the number of nanoparticles 11 closest to one nanoparticle 11 is equivalent to the number of nanoparticles 11 combined by the crosslinking portion 21.

[0067] It should be noted that the number of nanoparticles 11 closest to one nanoparticle 11, that is, the number of nanoparticles 11 bound via the crosslinking portion 21, refers to the number of other nanoparticles 11 bound to one nanoparticle 11 via the crosslinking portion 21. For example, in the case where a certain nanoparticle 11 is bound to only one other nanoparticle 11 via a plurality of crosslinking portions 21, the number of nanoparticles 11 bound to the nanoparticle 11 via the crosslinking portion 21 is one. The “number of nanoparticles 11 closest to one nanoparticle 11” is obtained by determining the simple average value (arithmetic mean) of the number of other nanoparticles 11 bound to each of the 50 nanoparticles 11 thus determined via the crosslinking portion 21.

[0068] Furthermore, when the component analysis and composition analysis of the porous membrane 1 are performed using the above-mentioned FT-IR, GC, XPS, NMR, and EDX, in the case where a component other than the nanoparticles 11 and the organic silane molecules 12 (silane linker) coating the nanoparticles 11 is detected, it can be considered that the component is derived from the crosslinking portion 21. Therefore, it can be understood that the crosslinking portion 21 including the component exists between the nanoparticles 11.

[0069] (1-2. Method for producing porous film)

[0070] Figure 7 A flow chart showing the steps of manufacturing the porous membrane 1. Hereinafter, a description is first given of a method of manufacturing the porous membrane 1 in which a plurality of nanoparticles 11 are directly connected to each other through the crosslinking portion 21.

[0071] (Synthesis of Nanoparticles)

[0072] First, nanoparticles 11 (e.g., silica particles) are synthesized using a liquid phase method (step S101). In general, methods for manufacturing silica nanoparticles are roughly divided into two types: a gas phase method and a liquid phase method. As described above, fine nanoparticles 11 with a diameter of less than 11 nm can be separated without causing aggregation by using a liquid phase method. As a precursor in the liquid phase method, it is preferred to select a molecule represented by the following general formula (7) that can form a three-dimensional polysiloxane skeleton (Si-O-Si) through a hydrolysis reaction and a condensation reaction. Examples of such precursors include water glass (soda silicate (sodium silicate)) and alkoxysilane molecules. Alkoxysilane molecules can be molecules in which some alkoxy groups are substituted by non-hydrolyzable functional groups, and do not hinder the formation of the polysiloxane skeleton.

[0073] (Chemical Formula 7) R 6 Z Si(OR 7 ) 4-Z (7)

[0074] (R 6It is any one of methyl, ethyl, propyl, isopropyl, butyl, pentyl, hexyl, heptyl, octyl, decyl, dodecyl, hexadecyl, vinyl, phenyl, acryloyloxy, methacryloyloxy, aminopropyl, glycidoxypropyl, and mercaptopropyl. 7 is any of a hydrogen atom, a methyl group, an ethyl group, a propyl group and an isopropyl group. Z is an integer of 0 or 2 or less.

[0075] After the above-mentioned precursor is dissolved in water or an organic solvent, the acidity or alkalinity is adjusted. Thus, silica particles are formed by polymerization reaction. It should be noted that as long as the diameter of the final nanoparticle 11 is 11nm or less, the method is not limited to the above-mentioned manufacturing method. The following are examples of references. For example, document 1 (T. Yokoi et al. Chem. Mater. 2009, 21, 3719-3729) reports the formation of nanoparticles with a diameter of 8nm in an aqueous solution in the presence of amino acids, wherein the nanoparticles are coated with amino acid molecules, thereby enabling the separation of nanoparticles without causing their aggregation. Document 2 (S. Sakamoto et al. Langmuir 2018, 34, 1711-1717) reports the formation of nanoparticles with a diameter of 3nm by using a reverse micellar liquid crystal phase as a template, wherein the nanoparticle surface is coated with surfactant molecules, thereby enabling the separation of nanoparticles without causing nanoparticle aggregation.

[0076] (Surface modification of nanoparticles)

[0077] Next, the nanoparticles 11 are dispersed in a solvent to modify the surface (step S102). For example, amphiphilic molecules such as surfactant molecules, amino acid molecules, phospholipids or block copolymers of polyalkylene glycols and other polymers are added to the dispersion in which the nanoparticles 11 are dispersed. The added amphiphilic molecules are adsorbed on the surface of the nanoparticles 11 to prevent the nanoparticles from aggregating. As in the above-mentioned documents 1 and 2, according to the manufacturing method, nanoparticles 11 with amphiphilic molecules coated on the surface are obtained. In this case, the addition of amphiphilic molecules is omitted.

[0078] (Cross-linking between nanoparticles)

[0079] Subsequently, the nanoparticles 11 are cross-linked together using a cross-linking agent (silane compound) (step S103). In the dispersion liquid in which the nanoparticles 11 are dispersed, the above-mentioned silane compound having more than two reaction points is added as a cross-linking agent in a state where the surface is coated with surfactant molecules, amino acid molecules, polymers, etc. The amount of the silane compound to be added is not particularly limited. After the silane compound is added, the dispersion liquid is heated as needed. Therefore, in the dispersion liquid, the cross-linking reaction of the nanoparticles 11 proceeds to form a porous membrane 1 having a three-dimensional structure. The dispersion liquid gradually loses its fluidity and becomes a gel state.

[0080] (Water repellency of nanoparticle surface)

[0081] Next, the surface of the nanoparticles 11 is made waterproof (step S104). The above-mentioned organosilane compound containing an organic functional group or a fluorine group is added to the dispersion in which the nanoparticles 11 cross-linked by a cross-linking agent are dispersed. The amount of the organosilane compound to be added is not particularly limited. After the addition of the organosilane compound, the dispersion is heated as needed. Thus, the surface of the nanoparticles 11 is made waterproof.

[0082] (Drying of three-dimensional structures)

[0083] Finally, the dispersion that has entered the gel state is dried to obtain the porous membrane 1 (step S105). An embodiment of the method for drying and removing the solvent includes drying at a high temperature under normal pressure. In the case where there is a concern that the porous membrane 1 will decompose due to the interfacial tension during drying, it is preferred to use a supercritical drying method or a freeze-drying method. In this embodiment, the surface of the nanoparticles 11 (silica particles) that are the cause of the large interfacial tension is inactivated by coating with the organosilane molecules 12 containing organic functional groups or fluorine groups. Therefore, the porous membrane 1 is less likely to disintegrate during drying compared to the case where the surface is not coated. Therefore, the porous membrane 1 is obtained. Figure 1 The porous membrane 1 is shown.

[0084] Next, a description is given of a method of manufacturing the porous membrane 1 in which the plurality of nanoparticles 11 are bonded to each other via the organosilane molecules 12 through the crosslinking portions 21 .

[0085] (Synthesis of Nanoparticles)

[0086] First, in the same manner as the method for manufacturing the above-mentioned porous membrane 1, nanoparticles 11 (e.g., silica particles) are synthesized using a liquid phase method, in which a plurality of nanoparticles 11 are directly bonded to each other through a crosslinking portion 21. As a precursor in the liquid phase method, it is preferred to select a molecule represented by the above-mentioned general formula (7) that can form a three-dimensional polysiloxane skeleton (Si-O-Si) through a hydrolysis reaction and a polycondensation reaction. Examples of such precursors include water glass (silicate soda (sodium silicate)) and alkoxysilane molecules. The alkoxysilane molecule can be a molecule in which some alkoxy groups are substituted by non-hydrolyzable functional groups, and does not hinder the formation of the polysiloxane skeleton.

[0087] (Surface modification of nanoparticles)

[0088] Next, the nanoparticles 11 are dispersed in a solvent to modify the surface. Here, instead of surfactant molecules, amino acid molecules or polymers, organosilane molecules 12 (silane linkers) represented by the following general formula (8) or general formula (9) are added to the dispersion. After the silane linker is added, heating is performed as needed. This allows the nanoparticles 11 (silicon dioxide particles) and the organosilane molecules 12 to react with each other to form covalent bonds, thereby deactivating the surface of the nanoparticles 11 and preventing the aggregation of the nanoparticles 11. In addition, as in the present manufacturing method, in the case where the nanoparticles 11 are coated with organosilane molecules 12 on the surface, multiple nanoparticles 11 are connected to each other via the organosilane molecules 12 through the cross-linking portion 21. Therefore, the organosilane molecules 12 represented by the following general formula (8) or general formula (9) need to have reactive functional groups 13 to covalently bond with the cross-linking portion 21. Examples of the reactive functional group 13 include a vinyl group, a methacrylic group, an acrylic group, a glycidyl group, a mercapto group, an amino group, a hydrosilyl group, a hydroxyl group, a carboxyl group, a cyano group, and an amino group.

[0089] (Chemical formula 8) R 8 x Si(OR 9 ) 4-x (8)

[0090] (Chemical formula 9) R 8 x SiCl 4-x (9)

[0091] (R 8 R is any one of a hydrogen atom, a vinyl group, an acryloyloxy group, a methacryloyloxy group, an aminopropyl group, a glycidoxypropyl group, and a mercaptopropyl group. 9 is any one of methyl, ethyl, propyl and isopropyl. X is an integer of 3 or less. )

[0092] (Cross-linking between nanoparticles)

[0093] Next, the nanoparticles 11 are crosslinked using a crosslinking agent including two or more reactive functional groups. In the dispersion in which the nanoparticles 11 are dispersed, silane compounds such as the above-mentioned multifunctional allyl (vinyl), multifunctional thiol, multifunctional (meth) acrylate, and multifunctional glycidyl are added as a crosslinking agent, and organic silane molecules 12 are coated on each surface. After the silane compound is added, heating or light irradiation is performed as required. Thus, in the dispersion, a crosslinking reaction occurs with the organic functional groups of the organic silane molecules 12, thereby forming a porous membrane 1 having a three-dimensional structure. The dispersion gradually loses its fluidity and becomes a gel state. In the case where the crosslinking reaction is an organic reaction such as a free radical reaction, cationic polymerization, or anionic polymerization, a suitable reaction initiator can be added.

[0094] (Drying of three-dimensional structures)

[0095] Finally, in the same manner as the above-mentioned method for manufacturing the porous membrane 1 (wherein the plurality of nanoparticles 11 are directly bonded to each other via the crosslinking portion 21), the dispersion liquid that has entered the gel state is dried to obtain the porous membrane 1. As in the present manufacturing method, in the case where the nanoparticles 11 pre-coated with the organosilane molecules 12 are connected to each other via the crosslinking portion 21, the unreacted reactive functional groups 13 have hydrophobicity, and thus the above-mentioned waterproofing step (step S104) is omitted. Thus, the porous membrane 1 is obtained. Figure 1 The porous membrane 1 is shown.

[0096] (1-3. Work and Effect)

[0097] In the porous membrane 1 of the present embodiment, a plurality of nanoparticles 11 having surfaces coated with organic silane molecules 12 including organic functional groups or fluorine groups are bonded to each other via crosslinking portions 21. This prevents aggregation of the plurality of nanoparticles 11, thereby suppressing particle growth. This is described below.

[0098] The waterproof film is used as a protective sheet for preventing dripping, staining, and rust, as well as preventing the adhesion of fingerprints, imparting lubricity, and maintaining the texture of the material. The hydrophobic film is typically a coating such as a fluorine compound, silicone, a surfactant, or wax. Among them, fluorine compounds and silicones are particularly well known as hydrophobic films excellent in hydrophobicity and durability.

[0099] Incidentally, the hydrophobicity of the hydrophobic film is improved due to the surface concavoconvexity. The above-mentioned aerogel is expected to be used as an anti-reflection film due to its low refractive index and low dielectric constant. However, the transparency of the current aerogel is insufficient, and the generation of low product quality such as white turbidity or noise becomes a problem. This is due to the thickness of the aerogel skeleton.

[0100] Aerogels scatter light according to the thickness of the skeleton, and the scattering intensity is proportional to the sixth power of the particle size, for example. Aerogels are prepared, for example, as follows. First, a silica alkoxide precursor is dissolved in a solvent such as ethanol, and the particles are grown by hydrolysis and polycondensation polymerization to obtain nanoparticles. Afterwards, the nanoparticles are copolymerized together to form a skeleton and gelled. The resulting wet gel is supercritically dried to remove the solvent, for example, to obtain a porous aerogel. In the above-mentioned manufacturing method, particle growth is also carried out in the steps of skeleton formation and drying, thereby increasing the thickness of the skeleton of the aerogel and reducing transparency.

[0101] In contrast, in the present embodiment, the surface of the plurality of nanoparticles 11 is coated with an organic silane molecule 12 having an organic functional group or a fluorine group, and the nanoparticles 11 are bonded to each other through, for example, a crosslinking portion 21 containing a silane compound. This prevents the aggregation of the plurality of nanoparticles 11 and suppresses particle growth in the skeleton formation process and the drying process.

[0102] As described above, in the porous membrane 1 of the present embodiment, the plurality of nanoparticles 11 coated with the organic silane molecules 12 including the organic functional group or the fluorine group on the surface are bonded to each other through the crosslinking portion 21, thereby preventing the aggregation of the plurality of nanoparticles 11. Therefore, the porous membrane 1 having high light transmittance and high hydrophobicity can be provided.

[0103] In addition, in the present embodiment, before the plurality of nanoparticles 11 having a bead-like skeleton constituting the porous membrane 1 are bonded to each other by a crosslinking agent, the surface is coated with an amphiphilic molecule such as a surfactant molecule, an amino acid molecule or a macromolecule or an organic silane molecule. This makes it possible to prevent the plurality of nanoparticles 11 from aggregating in the crosslinking step and to suppress particle growth. Therefore, a porous membrane 1 having a higher transmittance can be provided.

[0104] Next, a modification of the above-described embodiment is described. Hereinafter, components similar to those in the foregoing embodiment are denoted by the same reference numerals, and description thereof is appropriately omitted.

[0105] <2. Modifications>

[0106] Figure 8 An example of the configuration of a porous membrane (porous membrane 1A) according to a modification of the present disclosure is schematically shown. In the same manner as the porous membrane 1 in the above-mentioned embodiment, for example, the porous membrane 1A is used as an anti-reflection film and a protective sheet for preventing dripping, anti-fouling, and rust, and preventing the adhesion of fingerprints, imparting lubricity, and maintaining the texture of the material. The porous membrane 1A of this modification is different from the above-mentioned embodiment in that a plurality of nanofibers 31 are used instead of a plurality of nanoparticles 11.

[0107] The nanofiber 31 is, for example, a fiber material having a length 100 times or more of the diameter, and is, for example, a silica nanofiber. The average diameter of the nanofiber 31 is The nanofiber 31 has an organic silane molecule 12 containing an organic functional group or a fluorine group, or an organic functional group or a fluorine group, in the same manner as the nanoparticle 11. The surface of the nanofiber 31 is coated with the organic silane molecule 12 containing a reactive functional group 13, so that the plurality of nanofibers 31 are in a state where they cannot be covalently bonded to each other.

[0108] In the same manner as in the previous embodiment, a plurality of nanofibers 31 are connected to each other via the cross-linking portion 21. The length of the cross-linking portion 21 is preferably smaller than the diameter of the nanofiber 31. This makes it possible to prevent aggregation of the plurality of nanofibers 31 inside the porous membrane 1A.

[0109] For example, nanofiber 31 is capable of forming silica nanofibers having a diameter of 5 nm to 10 nm by using a reverse micellar liquid crystal phase as a template (Document 3 (W.-C. Lai, L et al., Journal of the Chemical Engineering Society of Taiwan, 2019, Vol. 99, pp. 207-214)). In addition, for example, nanofiber 31 is capable of forming twisted rod-shaped silica nanofibers by utilizing self-assembly of aminopropyltrimethoxysilane (Document 4 (Y. Kaneko et al. Chem. Mater. 2004, 16, 3417-3423)).

[0110] It should be noted that the above-described manufacturing method is exemplary, and this is not limitative as long as the nanofiber 31 having a diameter of 11 nm or less is finally obtained.

[0111] For the surface modification of the nanofibers 31, the crosslinking between the nanofibers 31 using a crosslinking agent, and the hydrophobicity and drying of the surface of the nanofibers 31, the same method as the surface modification of the nanoparticles 11, the crosslinking between the nanoparticles 11 using a crosslinking agent, and the drying thereof can be used.

[0112] It should be noted that Figure 8 An example of a porous membrane 1A configured only by nanofibers 31 is shown, but this is not restrictive. Fig. 9 In the porous membrane 1B shown in FIG. 1 , the nanoparticles 11 and the nanofibers 31 may be present in a mixed manner. In this case, the nanoparticles 11 are linked to each other, and the nanofibers 31 are linked to each other, and the nanoparticles 11 and the nanofibers 31 are linked to each other via the crosslinking portion 21 described above.

[0113] As described above, in the porous membranes 1A and 1B of the present modification, some or all of the nanoparticles 11 are replaced by nanofibers 31. The surface thereof is coated with an organic silane molecule 12 including an organic functional group or a fluorine group, or an organic silane molecule 12 including an organic functional group or a fluorine group and also having a reactive functional group 13. The nanoparticles 11 and the nanofibers 31 are bonded to each other, or the nanofibers 31 are bonded to each other, for example, via a crosslinking portion 21 including a silane compound. Thus, it is possible to prevent the aggregation of a plurality of nanoparticles 11 between a plurality of nanofibers 31 and between the nanoparticles 11 and the nanofibers 31, and it is possible to suppress the growth of the skeleton. Note that a plurality of nanoparticles 11 and a plurality of nanofibers 31 constitute the porous membrane 1A and the porous membrane 1B. Therefore, it is possible to obtain an effect similar to that of the above-described embodiment.

[0114] Although the description of the present disclosure has been given above with reference to the embodiments and variations, the present disclosure is not limited to the above-mentioned embodiments, etc., and can be modified in various ways. For example, the above-mentioned embodiments, etc. illustrate silica particles as nanoparticles 11 and silica nanofibers as nanofibers 31, but this is not restrictive. Nanoparticles or nanofibers containing inorganic oxides, inorganic nitrides, inorganic carbides or organic substances can also be used. In addition, for example, the porous membrane of the present invention (e.g., porous membrane 1) can be configured by various types of nanoparticles and / or nanofibers, wherein the above-mentioned materials are appropriately selected.

[0115] In addition, as application examples of the porous membrane 1, the aforementioned embodiments and the like illustrate anti-reflection films and protective sheets for preventing dripping, dirt and rust, preventing fingerprint adhesion, imparting lubricity, and maintaining the texture of the material. However, the porous membrane 1 and the like of the present disclosure can be used as functional components other than protective sheets and anti-reflection films of other electronic devices and the like. For example, the use of a block structure allows applications similar to those of typical porous materials, such as thermal insulation materials; adsorbents for odorous components, bacteria, and viruses; hygroscopic materials that control the air humidity to be constant; and sound-absorbing materials that prevent sound waves from traveling. In addition, the porous membrane 1 can be used for applications that require transparency, and is therefore suitable for structural materials for electronic devices such as photocatalysts, artificial photosynthesis, solar cells, or semiconductors in addition to low dielectric constant films and the like.

[0116] It should be noted that the effects described herein are merely exemplary and should not be limited thereto, and other effects may also be included.

[0117] It should be noted that the present technology may also have the following configuration. According to the present technology configured below, a plurality of nanoparticles or a plurality of nanofibers coated with organic silane molecules including organic functional groups or fluorine groups are connected to each other via a crosslinking portion. This prevents the aggregation of a plurality of nanoparticles or a plurality of nanofibers and inhibits the growth of particles. Therefore, a porous film with high light transmittance and high hydrophobicity can be provided.

[0118] (1) A nanomaterial structure comprising:

[0119] Nanomaterials, including nanomaterial surfaces;

[0120] providing an organosilane compound on the surface of the nanomaterial; and

[0121] The nanomaterial cross-linking portion includes a nanomaterial cross-linking portion and a nanomaterial cross-linking portion. (2)

[0123] The nanomaterial structure according to (1), wherein the nanomaterial and the nanomaterial cross-linking portion are directly or indirectly cross-linked via covalent bonds. (3)

[0125] The nanomaterial structure according to (1) or (2), wherein the nanomaterial cross-linking portion comprises an organic material or an inorganic material covalently bonded to the nanomaterial. (4)

[0127] The nanomaterial structure according to any one of (1) to (3), wherein the nanomaterial crosslinking portion includes a silane compound. (5)

[0129] The nanomaterial structure according to any one of (1) to (4), wherein the nanomaterial cross-linking portion is bonded to the nanomaterial at one or two locations. (6)

[0131] The nanomaterial structure according to any one of (1) to (4), wherein the nanomaterial crosslinking portion is indirectly bonded to the nanomaterial via an organic silane compound provided on the surface of the nanomaterial. (7)

[0133] The nanomaterial structure according to any one of (1) to (6), wherein the length of the crosslinked portion of the nanomaterial is less than 1 / 2 of the average particle diameter of the nanomaterial. (8)

[0135] The nanomaterial structure according to any one of (1) to (7), wherein the average particle size of the nanomaterial is 11 nm or less. (9)

[0137] The nanomaterial structure according to any one of (1) to (7), wherein the average particle size of the nanomaterial is 7 nm or less. (10)

[0139] The nanomaterial structure according to any one of (1) to (9), wherein the nanomaterial includes at least one of a plurality of nanoparticles, nanofibers or nanosheets, the nanoparticles, nanofibers or nanosheets having a surface coated with an organic silane compound and cross-linked with the nanomaterial cross-linking portion. (11)

[0141] The nanomaterial structure according to any one of (1) to (10), wherein the organic silane compound includes one or more of an organic functional group or a fluorine group. (12)

[0143] A porous membrane comprising:

[0144] Nanomaterials, including nanomaterial surfaces;

[0145] providing an organosilane compound on the surface of the nanomaterial; and

[0146] The nanomaterial cross-linking portion includes a nanomaterial cross-linking portion and a nanomaterial cross-linking portion. (13)

[0148] The porous film according to (12), wherein the porous film is an antireflection film or a protective sheet. (14)

[0150] A porous material comprising:

[0151] Nanomaterials, including nanomaterial surfaces;

[0152] providing an organosilane compound on the surface of the nanomaterial; and

[0153] The nanomaterial cross-linking portion includes a nanomaterial cross-linking portion and a nanomaterial cross-linking portion. (15)

[0155] The porous material according to (14), wherein the porous material is a heat insulating material, an adsorbent material, a hygroscopic material, a sound absorbing material, a transparent material including a photocatalyst material, an artificial photosynthesis material, a material for electronic devices including a solar cell material, a semiconductor material or a low dielectric constant film material. (16)

[0157] A method of manufacturing a material, comprising:

[0158] providing a nanomaterial comprising a nanomaterial surface; and

[0159] An organosilane compound is provided on the surface of the nanomaterial to form a coated nanomaterial. (17)

[0161] The method according to (16), further comprising:

[0162] providing a cross-linking agent; and

[0163] The nanomaterial cross-linked structure is formed by cross-linking the coated nanomaterial with a cross-linking agent. (18)

[0165] The method according to (17), further comprising:

[0166] Cross-linked structure of dry nanomaterials. (19)

[0168] The method according to (17), further comprising:

[0169] The porous membrane or porous material is formed by the cross-linked structure of the nanomaterials. (20)

[0171] According to the method of (19), the porous film or porous material is an anti-reflection film, a protective sheet, a heat insulating material, an adsorbent material, a hygroscopic material, a sound absorbing material or a transparent material including a photocatalyst material, an artificial photosynthesis material, a material for electronic devices including a solar cell material, a semiconductor material or a low dielectric constant film material. (twenty one)

[0173] A method for manufacturing a nanomaterial structure, comprising:

[0174] providing a nanomaterial including a nanomaterial surface and an organosilane compound disposed on the nanomaterial surface;

[0175] providing a cross-linking agent; and

[0176] The nanomaterial structure is formed by cross-linking the nanomaterial with a cross-linking agent. (twenty two)

[0178] A method for manufacturing a nanomaterial structure, comprising:

[0179] The nanomaterial structure is formed by drying the nanomaterial cross-linked structure, wherein the nanomaterial cross-linked structure includes the nanomaterial, the nanomaterial includes a nanomaterial surface and an organic silane compound disposed on the nanomaterial surface, wherein the nanomaterial is cross-linked with a cross-linking agent. (twenty three)

[0181] A method of manufacturing a product, comprising:

[0182] A product is formed from a nanomaterial structure, wherein the nanomaterial structure includes a nanomaterial, the nanomaterial includes a nanomaterial surface and an organosilane compound disposed on the nanomaterial surface, wherein the nanomaterial is crosslinked with a crosslinking agent, and wherein the nanomaterial structure has been dried. (twenty four)

[0184] A porous membrane comprising:

[0185] a plurality of nanoparticles or a plurality of nanofibers whose surfaces are coated with organic silane molecules including organic functional groups or fluorine groups; and

[0186] The cross-linking portion connects a plurality of nanoparticles or a plurality of nanofibers to each other. (25)

[0188] The porous membrane according to (24), wherein the nanoparticles or nanofibers and the cross-linking portion form a covalent bond. (26)

[0190] The porous membrane according to (24) or (25), wherein the cross-linking portion comprises an organic substance or an inorganic substance directly covalently bonded to the nanoparticles or nanofibers. (27)

[0192] The porous membrane according to (24) or (25), wherein the cross-linking portion includes an organic substance or an inorganic substance covalently bonded to the nanoparticles or nanofibers via a silyl group. (28)

[0194] The porous membrane according to any one of (24) to (27), wherein the cross-linking portion is bonded to the nanoparticles or nanofibers at one or two locations. (29)

[0196] The porous film according to any one of (24) to (28), wherein the length of the cross-linked portion is less than 1 / 2 of the average particle diameter of the plurality of nanoparticles. (30)

[0198] The porous membrane according to any one of (24) to (28), wherein the length of the cross-linked portion is less than 1 / 2 of an average diameter of the plurality of nanofibers. (31)

[0200] The porous membrane according to any one of (24) to (29), wherein an average particle diameter of the plurality of nanoparticles is 11 nm or less. (32)

[0202] The porous membrane according to any one of (24) to (29), wherein an average particle diameter of the plurality of nanoparticles is 7 nm or less. (33)

[0204] The porous membrane according to any one of (24) to (28) or (30), wherein an average diameter of the plurality of nanofibers is 11 nm or less. (34)

[0206] The porous membrane according to any one of (24) to (33), wherein

[0207] The porous membrane includes both a plurality of nanoparticles and a plurality of nanofibers, and

[0208] The nanoparticles and nanofibers are partially connected via the crosslinking portion. (35)

[0210] A method for manufacturing a porous membrane, the method comprising:

[0211] By adding a cross-linking agent, a plurality of nanoparticles or a plurality of nanofibers are connected to each other via a cross-linking portion containing the cross-linking agent; and

[0212] The surfaces of the plurality of nanoparticles or the plurality of nanofibers are modified by adding an organosilane molecule including an organic functional group or a fluorine group. (36)

[0214] A method for manufacturing a porous membrane according to (35), wherein amphiphilic molecules or organosilane molecules are added to a dispersion in which multiple nanoparticles or multiple nanofibers are dispersed, and adsorbed onto the surfaces of the multiple nanoparticles or multiple nanofibers before connection between the multiple nanoparticles or between the multiple nanofibers. (37)

[0216] A structure comprising:

[0217] a plurality of nanoparticles or a plurality of nanofibers whose surfaces are coated with organic silane molecules including organic functional groups or fluorine groups; and

[0218] The cross-linking portion connects a plurality of nanoparticles or a plurality of nanofibers to each other.

[0219] The present technology relates to Goal 13 "Climate Action" and Goal 07 "Affordable Clean Energy" in the SDGs (Sustainable Development Goals) adopted by the United Nations Summit in 2015, including nanomaterials and their applications in view of the structure and characteristics of the nanomaterial structure. For example, the nanomaterial structure is transparent and has thermal insulation properties, making it ideal for use in (e.g., as applied to the surface) any suitable glass material (e.g., windows, such as windows for residential, commercial and vehicle use (e.g., cars)) for energy efficiency purposes. In traditional glass materials, there is a problem that the energy consumption for indoor air cooling / heating purposes increases due to the large amount of heat flowing into / out of the window during the indoor air heating / cooling process. By using the nanomaterial structure of the present technology with a suitable glass material (e.g., window), less energy consumption should be required for indoor air heating / cooling purposes, thereby further contributing to the reduction of CO2 emissions from power generation using the combustion of fossil fuels. In addition, for example, the nanomaterial structure of the present technology can be used as a transparent plate for a solar collector to improve the energy efficiency (e.g., heat collection efficiency) of the solar collector, thereby contributing to the reduction of energy consumption from fossil fuels, thereby reducing CO2 emissions.

[0220] It should be understood by those skilled in the art that various modifications, combinations, sub-combinations and alterations may occur depending on design requirements and other factors insofar as they are within the scope of the appended claims or the equivalents thereof.

[0221] Reference Numbers List

[0222] 1.1A, 1B porous membrane

[0223] 11 Nanoparticles

[0224] 12 Organosilane molecules

[0225] 13 Reactive functional groups

[0226] 21 Cross-linking

[0227] 31 Nanofibers.

Claims

1. A nanomaterial structure, comprising: Nanomaterials, including nanomaterial surfaces; providing an organosilane compound on the surface of the nanomaterial; as well as The nanomaterial cross-linking portion, wherein the nanomaterial is cross-linked with the nanomaterial cross-linking portion. 2 . The nanomaterial structure according to claim 1 , wherein the nanomaterial and the nanomaterial cross-linking portion are directly cross-linked or indirectly cross-linked via covalent bonds. 3 . The nanomaterial structure according to claim 2 , wherein the nanomaterial cross-linking portion comprises an organic material or an inorganic material covalently bonded to the nanomaterial. The nanomaterial structure according to claim 3 , wherein the nanomaterial cross-linking portion comprises a silane compound. The nanomaterial structure according to claim 4 , wherein the nanomaterial cross-linking portion is combined with the nanomaterial at one or two locations. The nanomaterial structure according to claim 4 , wherein the nanomaterial cross-linking portion is indirectly combined with the nanomaterial via an organic silane compound provided on the surface of the nanomaterial. The nanomaterial structure according to claim 1 , wherein the length of the nanomaterial cross-linking portion is less than 1 / 2 of the average particle size of the nanomaterial. The nanomaterial structure according to claim 1 , wherein the average particle size of the nanomaterial is less than 11 nm. 9 . The nanomaterial structure according to claim 1 , wherein the average particle size of the nanomaterial is less than 7 nm.

10. The nanomaterial structure according to claim 1, wherein the nanomaterial comprises at least one of a plurality of nanoparticles, nanofibers and nanosheets, the nanoparticles, nanofibers or nanosheets having a surface coated with the organic silane compound and cross-linked with the nanomaterial cross-linking portion. The nanomaterial structure according to claim 10 , wherein the organic silane compound comprises one or more of an organic functional group or a fluorine group.

12. A porous membrane comprising: Nanomaterials, including nanomaterial surfaces; providing an organosilane compound on the surface of the nanomaterial; as well as The nano material cross-linking portion, wherein the nano material is cross-linked with the nano material cross-linking portion. 13 . The porous film according to claim 12 , wherein the porous film is an antireflection film or a protective sheet.

14. A porous material comprising: Nanomaterials, including nanomaterial surfaces; providing an organosilane compound on the surface of the nanomaterial; as well as The nano material cross-linking portion, wherein the nano material is cross-linked with the nano material cross-linking portion.

15. The porous material according to claim 14, wherein the porous material is a heat insulating material, an adsorbent material, a hygroscopic material, a sound absorbing material, a transparent material including a photocatalyst material, an artificial photosynthesis material, a material for electronic devices including a solar cell material, a semiconductor material or a low dielectric constant film material.

16. A method of manufacturing a material, comprising: providing a nanomaterial including a nanomaterial surface; as well as An organosilane compound is provided on the surface of the nanomaterial to form a coated nanomaterial.

17. The method according to claim 16, further comprising: providing a cross-linking agent; as well as A nanomaterial cross-linked structure is formed by cross-linking the coated nanomaterial with the cross-linking agent.

18. The method according to claim 17, further comprising: The nanomaterial cross-linked structure is dried.

19. The method according to claim 17, further comprising: The cross-linked structure of the nanomaterial forms a porous film or a porous material.

20. The method according to claim 19, wherein the porous membrane or the porous material is an anti-reflection film, a protective sheet, a heat insulating material, an adsorbent material, a hygroscopic material, a sound absorbing material, or a transparent material including a photocatalyst material, an artificial photosynthesis material, a material for electronic devices including a solar cell material, a semiconductor material or a low dielectric constant film material.

21. A method for manufacturing a nanomaterial structure, comprising: providing a nanomaterial including a nanomaterial surface and an organosilane compound disposed on the nanomaterial surface; providing a cross-linking agent; as well as The nanomaterial structure is formed by cross-linking the nanomaterial with the cross-linking agent.

22. A method for manufacturing a nanomaterial structure, comprising: The nanomaterial structure is formed by drying a nanomaterial cross-linked structure, wherein the nanomaterial cross-linked structure comprises a nanomaterial, the nanomaterial comprises a nanomaterial surface and an organic silane compound provided on the nanomaterial surface, and wherein the nanomaterial is cross-linked with a cross-linking agent.

23. A method of manufacturing a product, comprising: A product is formed from a nanomaterial structure, wherein the nanomaterial structure comprises a nanomaterial, the nanomaterial comprises a nanomaterial surface and an organosilane compound provided on the nanomaterial surface, wherein the nanomaterial is crosslinked with a crosslinking agent, and wherein the nanomaterial structure has been dried.

Citation Information

Patent Citations

  • Method for delivering article using mobile body that autonomously travels

    JP2022108615A